The use of chemometrics in combination with molecular spectroscopic and chromatographic methods for authentication of Curcuma species: a review - A., Rohman; E.A., Rawar; Sudevi, Sri; A.F, Nurrulhidayah; A., Windarsih (2020)
Currently, the awareness and public concern in the authenticity of herbal medicines has increased significantly, therefore, analytical methods capable of detecting the adulteration practice must be available. The rhizomes of Curcuma species such as Curcuma longa and Curcuma xanthorriza are the target of adulteration due to its popularity as components in herbal medicine formulation. For the sake of quality control of herbal medicines, a rapid and reliable method must be developed for authentication studies. Molecular spectroscopy including UV-Vis, infrared (near and mid) and 1H-NMR spectroscopy, as well as chromatographic-based methods especially liquid chromatography, can be an ideal method for herbal authentication due to its simplicity, however, the spectra and chromatogram obtained are usually complex which are difficult to interpret. To overcome this obstacle, a statistical approach known as chemometrics was used to treat spectra data to be easily used for authentication purposes including discrimination and classification between authentic and adulterated herbal components. This review highlighted molecular spectroscopic method in combination with multivariate data analysis (chemometrics) for authentication of herbal components.